Examination of risk factors for the beginning of alcohol use according to developmental periods in alcohol dependent subjects - İlhan, İnci Özgür and Doğan, Yıldırım B. and Demirbaş, Hatice and Boztaş, M. Hamid (Journal of Dependence, 2002)
Objective: It was aimed to examine the risk factors for alcohol use according to different developmental periods. The significance of the family history of alcohol use and peer group effects in beginning of drinking behaviour has been detected and the relationship between the presence of such factors with drinking behaviour has been examined. Method: The evaluation of 164 in- or outpatient alcohol dependent subjects has been done retrospectively. The sociodemographic data and history of alcohol use were collected by a data form. Chi-square test, logistic regression, oneway ANOVA and Mann Whitney U fests have been used for statistical analysis. Results: The major factor for the beginning of drinking behaviour appeared to be the peer group effect. The relationship between the presence of the family history of alcohol use the first degree relatives and referring that person in the family as the reason for drinking was found statistically significant. When the family history of alcohol problems and peer influence were taken together, the former factor was statisficaly significant for the childhood beginners. Besides, alcohol severity scores (estimated according to the frequency and the dosage of alcohol use) were significantly higher in the subjects with a positive family history of alcohol use. However if did not differ between those with a positive alcohol use history in the first degree relatives and those with a family history of alcohol use problems in the second degree relatives. Conclusion: In this study the influence of herritable factors and the social learning is noticable. Related with the social learning theory the presence of the family history of alcohol use forms a distinct risk factor for childhood period than the others.